Fracture Assessment of Blunt V-Notched Graphite Specimens by Means of the Strain Energy Density - Torabi, A.R.; Bertoh, F. (Проблемы прочности, 2013)
The main aim of the present work is to check
the suitability of the brittle fracture model,
namely the local strain energy density (SED), in
predicting the experimental results on mode I
fracture of blunt V-notched graphite components.
For this purpose, a wide range of test results
reported in the recent literature on brittle
fracture of V-notched test specimens characterized
by different geometries is considered. The
specimens are made of the same type of coarsegrained
polycrystalline graphite. The fracture assessment
is carried out predicting theoretically
the fracture loads by means of the SED criterion.
The SED parameter is evaluated by averaging
the local energy over a well-defined control
volume which embraces the notch edge. It is
found that the SED criterion allows assessing
the fracture behavior of graphite specimens
characterized by different notch angles and tip
radii. Проводится контроль пригодности модели хрупкого разрушения, а именно: локальной плотности энергии деформации, при прогнозировании результатов экспериментальных исследований по разрушению нормальным отрывом графитовых образцов с тупым V-образным
надрезом. Рассмотрены результаты испытаний на хрупкое разрушение образцов с V-образным надрезом с разной геометрией, представленные в литературных источниках. Образцы
изготовляли из однотипного крупнозернистого поликристаллического графита. Оценку разрушения проводили посредством теоретического прогнозирования разрушающей нагрузки с
помощью критерия плотности энергии деформации. Параметр плотности энергии деформации вычислен путем усреднения значения локальной энергии по определенному контрольному объему, который охватывает кромку надреза. Обнаружено, что данный критерий
позволяет оценивать поведение графитовых образцов с разными углами надреза и радиусами
у его вершины при разрушении. Проводиться контроль придатності моделі крихкого руйнування, а саме: локальної густини енергії деформації, при прогнозуванні результатів експериментальних досліджень щодо руйнування нормальним відривом графітових
зразків із тупим V-подібним надрізом. Розглянуто результати випробувань на
крихке руйнування зразків із V-подібним надрізом із різною геометрією,
відомі з літературних джерел. Зразки виготовляли з однотипного крупнозернистого полікристалічного графіту. При оцінці руйнування використовували теоретичне прогнозування руйнівного навантаження за допомогою
критерію густини енергії деформації. Параметр густини енергії деформації
обчислено шляхом усереднення значення локальної енергії за визначеним
контрольним об’ємом, що охоплює кромку надрізу. Установлено, що даний
критерій дозволяє оцінити поведінку графітових зразків із різними кутами
надрізу і радіусами у його вершині при руйнуванні.